Rationality of Analysts' Earnings Forecasts: UK Evidence - Pan, Yixuan (2008)
Analysts play crucial role in capital market. However, numerous prior researches provide evidence that analysts' earning forecasts are not efficient with respect to new information. Basu and Markov (2004) re-examine the efficiency of analysts' earning forecasts using both quadratic loss function and linear loss function. They argue that the forecasts are economically efficient under linear loss function. This dissertation replicates Basu and Markov (2004) method to examine the analysts'earnings forecast efficiency in UK market. The similar findings as Basu and Markov (2004) are obtained in my UK samples. The estimators of linear loss function is much closer to their predicted values than the estimators of quadratic loss function, and none of them are economically significant, indicating the analysts' earnings forecasts in UK market are economically efficient under linear loss function.